Does language prestige hypothesis hold true across typologically distant languages? A corpus-based study comparing shining-through effect in English-Chinese bidirectional translations - Jia Li; Yunhao Pan (PLoS ONE, 2026)
While the influence of language prestige on the source language shining through has been well-documented in studies involving typologically similar languages, its impact on typologically distant language pairs remains underexplored. This article examines the interplay between language prestige and typological differences in shaping the shining-through effect, extending the analysis to Chinese-English bidirectional translations. Based on a bidirectional parallel balanced corpus, the study compares the shining-through effect in both Chinese-to-English and English-to-Chinese translations through the application of principal component analysis and flexible discriminant analysis. The findings revealed that the shining-through effect was present in both translation directions but was more pronounced in English-to-Chinese translations. Additionally, the effect varied across registers, with imaginative texts showing a stronger tendency than the informative texts. These results provide further evidence supporting the hypotheses of language prestige, typological distance and risk aversion. A comparison with findings from studies involving typologically closer language pairs further suggests that typological distance may help explain variation in the influence of language prestige on source language shining through. Specifically, the prestige effect appears to be weaker when the source and target languages are typologically more distant, although this interpretation requires direct empirical testing in future research.